2022
DOI: 10.1111/iwj.13769
|View full text |Cite
|
Sign up to set email alerts
|

In situ cell electrospun using a portable handheld electrospinning apparatus for the repair of wound healing in rats

Abstract: Slow or non‐healing wounds caused by full‐thickness skin wounds of various origins have become a difficult challenge in clinical wound treatment. In particular, large full‐thickness skin wounds often lead to serious chronic skin wounds that do not heal. Electrospinning technology and stem cell treatment for wound repair have attracted much attention due to its unique advantages. In the current study, we electrospun polyvinyl alcohol (PVA) and bone marrow–derived stem cells (BMSCs) by a handheld electrospinning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 46 publications
0
20
0
Order By: Relevance
“…[ 179 ] Earlier this year, Xu et al. [ 180 ] described for the first time the in situ electrospinning of PVA NFs incorporating bone marrow‐derived stem cells (BMSCs) using a handheld apparatus for the treatment of non‐healing wounds. Zhang et al.…”
Section: Advanced Electrospinning Technologies: Needle‐basedmentioning
confidence: 99%
“…[ 179 ] Earlier this year, Xu et al. [ 180 ] described for the first time the in situ electrospinning of PVA NFs incorporating bone marrow‐derived stem cells (BMSCs) using a handheld apparatus for the treatment of non‐healing wounds. Zhang et al.…”
Section: Advanced Electrospinning Technologies: Needle‐basedmentioning
confidence: 99%
“…In recent studies, it has been shown that in situ electrospinning with handheld devices offers the following advantages over conventional systems (X.‐F. Liu, Zhang et al, 2020; Qin et al, 2020; Xu et al, 2022; Yue et al, 2021): the resulting mats adhere better to the wound area, particularly if this is irregular/uneven; storage/transport of the dressings is not required; bleeding and/or bacterial infections can be treated in emergency/outdoor situations; personalized dressings can be produced depending on the specific patient need. Examples of commercially available, portable, and battery‐operated electrospinning devices are: Spincare (Nanomedic Technologies Ltd.) that comes with prefilled, single‐use, and sterile cartridges; the products sold by Nanofiberlabs Co. Ltd and AME Energy Co. Ltd, which both can host a 5 mL disposable syringe and work at an output voltage of around 10 kV.…”
Section: Commercialization Of Electrospun Fibers For Skin/wound Carementioning
confidence: 99%
“…. In recent studies, it has been shown that in situ electrospinning with handheld devices offers the following advantages over conventional systems (X.-F Liu, Zhang et al, 2020;Qin et al, 2020;Xu et al, 2022;Yue et al, 2021):.…”
mentioning
confidence: 99%
“…For example, poly(vinyl alcohol) (PVA) is a water-soluble, organic polymer with excellent biocompatibility, biodegradability and processability [83]. Xu et al have studied the application of PVA in cell electrospinning for wound healing [69]. Since the synthetic materials lack appropriate cell adhesion features and sufficient bioactivity, some suggest semi-synthetic materials such as gelatin-methacryloyl (GelMA) that allow for the utilization of the biological signals innate to gelatin, as well as taking advantage of mechanical properties [73].…”
Section: Biofabrication Technologiesmentioning
confidence: 99%
“…The contribution of biofabrication technologies to cell therapy has been supported by an increasing body of literature. For example, biofabricated matrices control cell growth, migration, infiltration and differentiation through the sufficient recapitulation of the microenvironment physiologically relevant to the skin cells [78], and strong interaction with physicochemical properties, including porosity [75,76], topography [69,79] and crosslink density [72]. More details are found in previous reviews [10,11].…”
Section: Biofabrication Technologiesmentioning
confidence: 99%